Electromagnetic Radiation And Its Impact On Human Health: Control Methods And Regulatory Approaches (Eurasian Journal of History, Geography and Economics, 2025)
The article is devoted to the issues of control and regulation of electromagnetic radiation (EMR) in the radio frequency and ultra-high frequency ranges. Domestic and foreign devices for measuring electric and magnetic fields used in sanitary and hygienic practice and in the certification of workplaces are described in detail. Special attention is paid to current sanitary standards, state standards, and international requirements.